2015
DOI: 10.3233/cbm-140444
|View full text |Cite
|
Sign up to set email alerts
|

Association of TNF-α (-238 and -308) promoter polymorphisms with susceptibility of oral squamous cell carcinoma in North Indian population

Abstract: We conclude that the TNF-α (-238) G/A polymorphism was significantly associated with OSCC however TNF-α (-308) G/A polymorphism was not associated in OSCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
(38 reference statements)
3
15
0
Order By: Relevance
“…It has been reported to be associated with Cervical cancer, Gastric cancer, Oral cancer, Prostate cancer, Renal cell carcinoma, Bladder cancer, Hepatocellular carcinoma, Malignant melanoma and Non-Hodgkin's Lymphoma [3548]. However, no significant association was found for Nasopharyngeal carcinoma, Lung cancer, Gastric carcinoma, Myeloma, Basal cell carcinoma, Cervical cancer, Breast cancer and Oral squamous cell carcinoma [49–62]. The association between this polymorphism and these cancer risk can be found in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported to be associated with Cervical cancer, Gastric cancer, Oral cancer, Prostate cancer, Renal cell carcinoma, Bladder cancer, Hepatocellular carcinoma, Malignant melanoma and Non-Hodgkin's Lymphoma [3548]. However, no significant association was found for Nasopharyngeal carcinoma, Lung cancer, Gastric carcinoma, Myeloma, Basal cell carcinoma, Cervical cancer, Breast cancer and Oral squamous cell carcinoma [49–62]. The association between this polymorphism and these cancer risk can be found in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…The TNF-␣ codifies a potent immunomodulator and pro-inflammatory cytokine that mediates diverse pathological processes [11][12][13]. The gene that codifies for TNF-␣ contains several polymorphic sites, of which TNF-␣-238 (rs361525) and TNF-␣-308 (rs1800629) are studied widely [14][15][16]. It has been demonstrated that TNF-␣ promoter polymorphisms had association with susceptibility of many diseases, such as squamous cell carcinomas [16,17], hepatocellular carcinoma [18], but it is rarely seen about the family aggregation of gastric cancer and the change of gastric cancer susceptibility along with the relative degree through pedigree study.…”
Section: Introductionmentioning
confidence: 99%
“…The gene that codifies for TNF-␣ contains several polymorphic sites, of which TNF-␣-238 (rs361525) and TNF-␣-308 (rs1800629) are studied widely [14][15][16]. It has been demonstrated that TNF-␣ promoter polymorphisms had association with susceptibility of many diseases, such as squamous cell carcinomas [16,17], hepatocellular carcinoma [18], but it is rarely seen about the family aggregation of gastric cancer and the change of gastric cancer susceptibility along with the relative degree through pedigree study. Therefore, this study was to investigate the genetic susceptibility role of TNF-␣ promoter polymorphisms (-238 and -308 positions) in gastric cancer based on case-control family study in Henan Province of China, with high incidence of gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Demographic characteristics, lifestyle and disease status of OSCC patients are previously published ( Singh et al, 2014a , Singh et al, 2014b ), which included age (47.67 ± 12.67 and 43.1 ± 8.31), sexes [(80.51% male and 76.76% male), (19.49% female and 23.24% female)], height (162.33 ± 6.0 and 163.10 ± 5.65) and weight (55.86 ± 8.50 and 57.78 ± 7.58) in OSCC patients and controls respectively. In this study we also observed tobacco chewing (61.40%, 47.57%), smoking (30.51%, 21.62%) and alcohol consumption (13.97%, 11.35%) in OSCC patients and controls respectively.…”
Section: Resultsmentioning
confidence: 99%